Wild World of Wild Food Plants in Cambodia: The Utilization, Challenges, and Opportunities to Scaling up the Use of Wild Food Plants - Sovanna Seav; Sreynget Lo; Saren Ry; Channaty Ngang; Panha Pok; Gracie Catherine Pekarcik; Sovanneary Huot; David Ader; Ricky Bates; Pao Srean (AGRITROPICA : Journal of Agricultural Sciences, 2021)
Underexploited wild food plant (WFP) species have a high potential to contribute to nutritional and/or medicinal health, generate income, and sustain the environment. The objective of this study was to identify market-available WFP species and characterize their beneficial use and economic values in northwestern Cambodia. Two hundred seventy-five (275) retailers in Battambang and Siem Reap were interviewed to collect data on wild food plant species availability and their values. Thirty-four (34) plant species were identified as WFP species, including annual and perennial herbs, perennial shrubs, vines, and trees. Leave, shoots, stems, rhizomes, corms, flowers, and fruits were the parts of the plant used for cooked dishes. Most of the parts used (92.4%) were collected from the wild, while 7.6% were reported as cultivated. The plant species are high in vitamin A, C, a good source of minerals, and can be used as traditional medicine. To enhance health and alleviate the ‘hidden hunger’ of micronutrient malnutrition, Cambodia should promote the production and dietary incorporation of wild food plants rich in minerals and vitamins.